Performativitas Queer dalam Novel Calabai karya Pepi Al-Bayqunie (Keberagaman Gender Masyarakat Bugis dalam Karya Sastra): Performativity of Queer in Novel Calabai Written by Pepi Al-Bayqunie (Gender Diversity of Buginese on Literary Work) - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2020)
Literary works is an imitation of the reality of human life is represented in Calabai by Pepi Al-Bayqunie. This novel takes the setting of Buginese community lifein South Sulawesi. This research discusses the queer performativity in novel Calabai through queer theory from Judith Butler. According to Butler, performativity is a natural condition for man in displaying his (physical) body. Discussion about sex, gender, and sexual orientation is a social construct that can be fluid, unnatural, and unstable. Performativity queer in Calabai's narratives is characterized as a natural appearance and repeatedly displayed by the characters of the story considered queer, calabai and bissu. Bissu was constructed by culture as gender